Related Articles

# Class 11 RD Sharma Solutions – Chapter 12 Mathematical Induction – Exercise 12.2 | Set 2

• Last Updated : 20 May, 2021

### Question 17. a + ar + ar2 + … + arn-1  = a [(rn – 1)/(r – 1)], r ≠ 1

Solution:

Let P (n) = a + ar + ar2 + … + arn-1 = a [(rn – 1)/(r – 1)]

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12.

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

Step 1:

Now, let us check P(n) for n = 1.

P (1) = a = a (r1 – 1)/(r – 1)

or, a = a

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = a + ar + ar2 + … + ark-1 = a [(rk – 1)/(r – 1)]     … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

Then, a + ar + ar2 + … + ark-1 + ark

Now, putting the value (i), we get,

= a [(rk – 1)/(r – 1)] + ark              (using eq(i))

= a[rk – 1 + rk(r – 1)] / (r – 1)

= a[rk – 1 + rk+1 – r-k] / (r – 1)

= a[rk+1 – 1] / (r – 1)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 18. a + (a + d) + (a + 2d) + … + (a + (n – 1)d) = n/2 [2a + (n – 1)d]

Solution:

Let P (n) = a + (a + d) + (a + 2d) + … + (a + (n – 1)d) = n/2 [2a + (n – 1)d]

Step 1:

Now, let us check P(n) for n = 1.

P (1) = a = 1/2[2a + (1 – 1)d]

or, a = a

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = a + (a + d) + (a + 2d) + … + (a + (k – 1)d) = k/2 [2a + (k – 1)d]    … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

Then, a + (a + d) + (a + 2d) + … + (a + (k – 1)d) + (a + (k)d)

Now, putting the value eq(i), we get,

= k/2 [2a + (k – 1)d] + (a + kd)               (Using eq(i))

= [2ka + k(k – 1)d + 2(a + kd)] / 2

= [2ka + k2d – kd + 2a + 2kd] / 2

= [2ka + 2a + k2d + kd] / 2

= [2a(k + 1) + d(k2 + k)] / 2

= (k + 1)/2 [2a + kd]

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 19. 52n – 1 is divisible by 24 for all n ∈ N

Solution:

Let P(n) = 52n – 1 is divisible by 24

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 52 – 1 = 25 – 1 = 24

So, P(1) is true as P(n) is divisible by 24.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 52k – 1 is divisible by 24

or, 52k – 1 = 24λ   … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

i.e., 52(k+1) – 1 is divisible by 24

Or, 52(k+1) – 1 = 24μ

Then, 52(k + 1) – 1

= 52k.52 – 1

= 25.52k – 1

Now, putting the value eq(i), we get,

= 25.(24λ + 1) – 1           (Using eq(i))

= 25.24λ + 24

= 24λ

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 20. 32n + 7 is divisible by 8 for all n ∈ N

Solution:

Let P (n) =   32n + 7 is divisible by 8

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 32 + 7 = 9 + 7 = 16

So, P(1) is true as P(n) is divisible by 8.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 32k + 7 is divisible by 8

or, 32k + 7 = 8λ

or, 32k = 8λ – 7   … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

i.e., 32(k+1) + 7 is divisible by 8

or, 32k+2 + 7 = 8μ

Then,

= 32k+2 + 7

= 32k.32 + 7

= 9.32k + 7

Now, putting the value eq(i), we get,

= 9.(8λ – 7) + 7                     (Using eq(i))

= 72λ – 63 + 7

= 72λ – 56

= 8(9λ – 7)

= 8μ

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 21. 52n+2 – 24n – 25 is divisible by 576 for all n ∈ N

Solution:

Let P (n) = 52n+2 – 24n – 25 is divisible by 576

Step 1:

Now, let us check P(n) for n=1.

P (1) = 52.1 + 2 – 24.1 – 25 = 625 – 49 = 576

So, P(1) is true as P (n) is divisible by 576.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 52k+2 – 24k – 25 is divisible by 576

or, 52k+2 – 24k – 25 = 576λ  … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

i.e., 52k + 4 – 24(k + 1) – 25 is divisible by 576

or, 52k + 2 – 24k – 25 = 576λ

Then,

= 5(2k + 2) + 2 – 24(k + 1) – 25

= 52k+2.52 – 24k – 24 – 25

Now, putting the value eq(i), we get,

= (576λ + 24k + 25)25 – 24k – 49                   (using eq(i))

= 25. 576λ + 576k + 576

= 576(25λ + k + 1)

= 576μ

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 22. 32n + 2 – 8n – 9 is divisible by 8 for all n ∈ N

Solution:

Let P (n) = 32n + 2  – 8n – 9 is divisible by 8

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 32.1 + 2 – 8.1 – 9 = 81 – 17 = 64

So, P(1) is true as P (n) is divisible by 8.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 32k + 2 – 8k – 9 is divisible by 8

or, 32k + 2 – 8k – 9 = 8λ   … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

i.e., 32k + 4 – 8(k + 1) – 9 is divisible by 8

3(2k + 2) + 2 – 8(k + 1) – 9 = 8μ

Then,

= 32(k+1).32 – 8(k + 1) – 9

= (8λ + 8k + 9)9 – 8k – 8 – 9

Now, putting the value (i), we get,

= 72λ + 72k + 81 – 8k – 17              (using eq(i))

= 8(9λ + 8k + 8)

= 8μ

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 23. (ab)n = an bn for all n ∈ N

Solution:

Let P (n) = (ab)n = an bn

Step 1:

Now, let us check P(n) for n = 1.

P (1) = ab = ab

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = (ab)k = ak bk   … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

i.e., (ab)k+1 = ak+1.bk+1

Then,

= (ab)k+1

= (ab)k .(ab)

Now, putting the value eq(i), we get,

= (ak bk) (ab)                (using eq(i))

= (ak+1) (bk+1)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 24. n (n + 1) (n + 5) is a multiple of 3 for all n ∈ N.

Solution:-

Let P (n) = n (n + 1) (n + 5) is a multiple of 3

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1 (1 + 1) (1 + 5)

or, 2 × 6

or, 12

So, P(1) is true as P(n) is multiple of 3.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = k (k + 1) (k + 5) is a multiple of 3

or, k(k + 1) (k + 5) = 3λ   … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

i.e., (k + 1)[(k + 1) + 1][(k + 1) + 5] is a multiple of 3

or, (k + 1)[(k + 1) + 1][(k + 1) + 5] = 3μ

Then,

(k + 1) [(k + 1) + 1] [(k + 1) + 5]

= (k + 1) (k + 2) [(k + 1) + 5]

= [k (k + 1) + 2(k + 1)] [(k + 5) + 1]

= k (k + 1) (k + 5) + k(k + 1) + 2(k + 1) (k + 5) + 2(k + 1)

= 3λ + k2 + k + 2(k2 + 6k + 5) + 2k + 2

= 3λ + k2 + k + 2k2 + 12k + 10 + 2k + 2

= 3λ + 3k2 + 15k + 12

= 3(λ + k2 + 5k + 4)

= 3μ

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 25. 72n + 23n-3.3n-1 is divisible by 25 for all n ∈ N

Solution:

Let P (n) = 72n + 23n-3 . 3n-1 is divisible by 25

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 72 + 20.30

or, 49 + 1 = 50

So, P(1) is true as P (n) is divisible by 25.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 72k + 23k-3. 3k-1 is divisible by 25

or, 72k + 23k-3. 3k-1 = 25λ   … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

i.e., 72(k+1) + 23k. 3k is divisible by 25

or, 72k+2 + 23k. 3k = 25μ

Then,

72(k+1) + 23k. 3k

= 72k.72 + 23k. 3k

Now, putting the value (i), we get,

= (25λ – 23k-3. 3k-1) 49 + 23k. 3k                 (Using eq(i))

= 25λ. 49 – 23k/8. 3k/3. 49 + 23k. 3k

= 24×25×49λ – 23k . 3k . 49 + 24 . 23k.3k

= 24×25×49λ – 25 . 23k. 3k

= 25(24 . 49λ – 23k. 3k)

= 25μ

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 26. 2.7n + 3.5n – 5 is divisible by 24 for all n ∈ N

Solution:-

Let P (n) = 2.7n + 3.5n – 5 is divisible by 24

Step 1:

Now, let us check P(n) for n=1.

P (1) = 14 + 15 – 5 = 24

So, P(1) is true as P (n) is divisible by 24.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 2.7k + 3.5k – 5 is divisible by 24

or, 2.7k + 3.5k – 5 = 24q  … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

i.e., 2.7k+1 + 3.5k+1 – 5

⇒ 2.7.7k + 3.5.5k– 5

Now, we will add and subtract by 3.7.5k- 7.5,

or, 2.7.7k + 3.5.5k – 5 + 3.7.5k – 7.5 – (3.7.5k – 7.5)

or, 7(2.7k + 3.5k – 5) + 3.5.5k – 5 – (3.7.5k – 7.5)

Now from equation (1) we have

or, 7(24q) + 3.5.5k- 5 – 3.7.5k+ 7.5

or, 7(24q) – 2.3.5k- 5 + 35

or, 7(24q) – 2.3.5k+ 30

or, 7(24q) – 6(5k- 5)

Now, we know that (5k – 5) is a multiple of 4.

So we can write (4p) where (p) is from natural number.

or, 7(24q) – 6(4p)

or, 24(7q – p)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 27. 11n+2 + 122n+1 is divisible by 133 for All N ∈ N.

Solution:

Let P (n) = 11n+2+ 122n+1 is Divisible by 133

Step 1:

Now, let us check P(n) for n=1.

P (1) = 111+2 + 122+1= 1331 + 1728 = 3059

So, P(1) is true as P (n) is divisible by 133.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 11k+2+ 122k+1 is Divisible by 133

or, 11k+2+ 122k+1 = 133p  … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

i.e., 11k+3+ 122k+3

= 11k+2. 11 + 122k+1. 122 + 11. 122k+1 − 11. 122k+1

= 11 (11k+2 + 122k+1) + 122k+1(144 − 11)

Now from equation (i) we have

= 11. 133p + 122k+1. 133               [From eq(i)]

= 133 (11p + 122k+1)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 28. 1×1! + 2×2! + 3×3! +…+ n×n! = (n + 1)! – 1 for all n ∈ N

Solution:

Let P (n) = 1×1! + 2×2! + 3×3! +…+ n×n

Step 1:

Now, let us check P(n) for n=1.

P (1) = 1 × 1! = (2)! – 1 = 1

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = m,

P (k) = 1×1! + 2×2! + 3×3! +…+ m×m! = (m + 1)! – 1  … (i)

Step 3:

Now, we have to prove for P(m + 1) is true.

i.e., 1×1! + 2×2! + 3×3! +…+ m×m! + (m + 1)×(m + 1)!

So, = (m + 1)! – 1 + (m + 1) × (m + 1)!

= (m + 1)!(m + 1 + 1) – 1

= (m + 1)!(m + 2) – 1

= (m + 2)! – 1

So, P (n) is true for n = m + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 29. Prove that n3 – 7n + 3 is divisible by 3 for all n ∈ N.

Solution:

Let P(n) = n3 – 7n + 3 is divisible by 3

Step 1:

Now, let us check P(n) for n=1.

P(1) = 13 − (7 × 1) + 3 = 1 − 7 + 3 = −3

So, P(1) is true as P(n) is divisible by 3.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = k3 – 7k + 3 is divisible by 3

or, k3 – 7k + 3 = 3m  … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

i.e.,  = (k + 1)3 − 7 (k + 1) + 3

= k3 + 3k2 + 3k + 1 − 7k − 7 + 3

= k3 + 3k2 − 4k − 3

= k3 − 7k + 3 + 3k2 + 3k − 6

Now from equation (i), we have

= 3m + 3 (k2 + k + 2)

= 3 (m + k2 + k + 2)

= 3t              (Here, t is any integer)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 30. Prove that 1 + 2 + 22 + … + 2n = 2n+1 – 1 for all n ∈ N

Solution:

Let P (n) = 1 + 2 + 22 + … + 2n = 2n+1 – 1

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1 + 2 = 21+1 – 1

or, 3 = 3

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1 + 2 + 22 + … + 2k = 2k+1 – 1 … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

i.e., 1 + 2 + 22 + … + 2k+1 = 2k+2 – 1

So, 1 + 2 + 22 + … + 2k + 2k+1

Now from equation (i), we have

or, 2k+1 – 1 + 2k+1

or, 2.2k+1 – 1

or, 2k+2 – 1

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 31. 7 + 77 + 777 + … + 777 . . . . . . . . . . . n − Digits 7 = 7/81 (10 n+1 − 9n − 10)

Solution:

Let P (n) = 7 + 77 + 777 + … + 777 . . . . . . . . . . . n − Digits 7 = 7/81 (10 n+1 − 9n − 10)

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 7 = 7/81 (102 – 9 – 10)

or, 7 = 7/81 ( 100 – 19)

or, 7 = 7/81 (81)

or, 7 = 7

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) =  7 + 77 + 777 + … + 777 . . . . . . . . . . . k− Digits7 = 7/81 (10 k+1 − 9k − 10)  … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

i.e., 7 + 77 + 777 + … + 777 . . . . . . . . . . . (k + 1) − Digits7

So, it is basically G.P. (geometric progression) with k + 1 terms.

So, sum P(k + 1)

or, 7/9[9 + 99 + 999 + ……………..+ (k + 1) term]

or, 7/9 [10 – 1 + 100 – 1 +………………..+ (k + 1)term]

or, 7/9 [10 + 100 + 1000 +…………+ (k + 1)term – (1 + 1 + 1 +….+ (k + 1) times)]

or, 7/81 [10k+2 – 9(k+1) – 10]

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 32. Prove that (n7/7) + (n5/5) + (n3/3) + (n2/2) – (37/210)n is a positive integer for all n ∈ N.

Solution:

Let P(n) be (n7/7) + (n5/5) + (n3/3) + (n2/2) – (37/210)n

Step 1:

Now, let us check P(n) for n = 1.

So, P(1) = 1/7+1/5+1/3+1/2-37/210 =1

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = m,

So, let P(m) be (m7/7) + (m5/5) + (m3/3) + (m2/2) – (37/210)m

Now, (m7/7) + (m5/5) + (m3/3) + (m2/2) – (37/210)m = λ, where λ ∈ N is a positive integer.

Step 3:

Now, we have to prove for P(m+1) is true.

P(m + 1) = ((m + 1)7/7) + ((m + 1)5/5) + ((m + 1)3/3) + ((m + 1)2/2) – (37/210)(m + 1)

= 1/7(m7 + 7m6 + 21m5 + 35m4 + 35m3 + 21m2 + 7m + 1) +

1/5(m5 + 5m4 + 10m3 + 10m2 + 5m + 1) + 1/3(m3 + 3m2 + 3m + 1) +

1/2(m2 + 2m + 1) + 37/210(m + 1)

= (m7/7 + m5/5 + m3/3 + m2/2 − 37/210m) + m6 + 3m5 + 5m4 + 5m3 + 3m2 +

m + m4 + 2m3 + 2m2 + m + m2 + m + m + 1/7 + 1/5 + 1/3 + 1/2 – 37/210

= λ + 3m5 + 5m4 + 5m3 + 3m2 + m + m4 + 2m3 + 2m2 + m + m2 + m + m + 1

As λ is positive, so it is a positive integer.

So, P (n) is true for n = m + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

My Personal Notes arrow_drop_up